2021
DOI: 10.7196/sajbl.2021.v14i3.772
|View full text |Cite
|
Sign up to set email alerts
|

Public health emergency preparedness and response in South Africa: A review of recommendations for legal reform relating to data and biological sample sharing

Abstract: COVID-19 exposed flaws in the law regulating the sharing of data and human biological material (HBM). This poses obstacles to the epidemic response, which needs accelerated public health research and, in turn, efficient and legitimate HBM and data sharing. Legal reform and development are needed to ensure that HBM and data are shared efficiently and lawfully. Academics have suggested important legal reforms. The first is the clarification of the susceptibility of HBM and HBM derivatives to ownership, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The template has received criticism [17] and the fact that it is a guidance document only may cause sections of it to be regarded as unimportant and excluded by researchers when completing it. [18] We therefore advocate that a national DTA, that is POPIA compliant, complement the current SAMTA with a view to having one consolidated document for the transfer of samples and data in the long term, and propose the following roadmap to achieve this.…”
Section: Regulatory Framework For Sharing Data For Research In Samentioning
confidence: 99%
“…The template has received criticism [17] and the fact that it is a guidance document only may cause sections of it to be regarded as unimportant and excluded by researchers when completing it. [18] We therefore advocate that a national DTA, that is POPIA compliant, complement the current SAMTA with a view to having one consolidated document for the transfer of samples and data in the long term, and propose the following roadmap to achieve this.…”
Section: Regulatory Framework For Sharing Data For Research In Samentioning
confidence: 99%
“…Donrich Thaldar 1,2 Lukman Abdulrauf 1,3,4 Paul Ogendi 1,5 Amy Gooden 1 Dusty-Lee Donnelly 1 Beverley Townsend 1,6 as being inadequate, as Brand et al do. By contrast, Nigeria, Africa's largest economy 6 , includes Ghana in its adequacy list (the South African Information Regulator has not yet issued a South African adequacy list).…”
Section: Authorsmentioning
confidence: 97%
“…In 2021, Steytler and Thaldar published a review of recommendations for legal reform in South Africa relating to, inter alia, data sharing during public health emergencies. 1 These recommendations include, in respect of health data: (a) the creation of an African Data Corridor, (b) the adoption of open access research data, and (c) the development of data trusts, as suggested by the Organisation for Economic Co-operation and Development (OECD), and in respect of geospatial data used for health research: (d) an amendment to the Space Affairs Act 84 of 1993. 1 Recommendations (a) to (c) were based on the work of Townsend 2 , and (d) on the work of Botes 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The only saving grace was that the SA MTA described itself as a “framework,” hence leaving latitude for parties that are legally forced to use it to amend the substantive provisions—and hopefully in the process resolve the problematic aspects ( Thaldar et al, 2020 ; Steytler and Thaldar, 2021 ; Thaldar and Shozi, 2021 ; Swales et al, 2023a ). Using this latitude, a group of South African law academics developed a revised version of the SA MTA in an attempt to rectify the most serious issues while remaining within the bounds of the framework of the original version of the SA MTA ( Pope, 2020 ).…”
Section: Introductionmentioning
confidence: 99%